2003
DOI: 10.1089/107632703764664800
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Phosphate—Chitosan Composite Scaffolds for Bone Tissue Engineering

Abstract: Macroporous calcium phosphate-chitosan composite scaffolds were fabricated and evaluated for use in bone tissue engineering. Human osteoblast-like MG63 cells were cultured on the composite scaffolds, and their response to the materials was studied. Cell morphology, total protein content, and expression of classic markers for osteoblast differentiation were characterized. MG63 cells on the hydroxyapatite scaffolds nesting chitosan sponges (HC1) showed significantly higher alkaline phosphatase (ALP) level and os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(108 citation statements)
references
References 20 publications
2
102
0
4
Order By: Relevance
“…Various biocomposites of calcium orthophosphates with chitosan 298,482,500,512,527,565,[645][646][647][648][649][650][651][652][653]674,675,690,695,799,807,[811][812][813][814][815][816][817][818][819][820][821][822][823][824][825][826][827][828] and chitin 232,476,612,[829][830][831][832][833] are also very popular. For example, a solutionbased method was developed to combine HA powders with chitin, in which the ceramic particles were uniformly dispersed.…”
Section: 725mentioning
confidence: 99%
“…Various biocomposites of calcium orthophosphates with chitosan 298,482,500,512,527,565,[645][646][647][648][649][650][651][652][653]674,675,690,695,799,807,[811][812][813][814][815][816][817][818][819][820][821][822][823][824][825][826][827][828] and chitin 232,476,612,[829][830][831][832][833] are also very popular. For example, a solutionbased method was developed to combine HA powders with chitin, in which the ceramic particles were uniformly dispersed.…”
Section: 725mentioning
confidence: 99%
“…Chitosan is biodegradable and biocompatible and is becoming more prevalent in the drug delivery arena [1,7,17,19,25,40,43]. Chitosan has been used as a material incorporated into implantable scaffolds in several studies [39,[41][42][43]. Further studies demonstrate chitosan is bacteriostatic and enhances wound healing rates [8,19,25,35,38].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that osteoblasts embedded in the CTS/HAp scaffolds are activated after 30 min and after 5 days they will start to aggregate the bone reconstruction process. 28 Kawakami et al studied the in vivo effect of CTS/HAp self-hardening paste through its application on the surface after removal of the periosteum. New bone formation was observed after 1 week and continued during a 20-week follow-up.…”
Section: Composite Chitosan-hydroxyapatitementioning
confidence: 99%